A new species of Emilia (Asteraceae, Senecioneae) from Lower Juba region, Somalia. (28th June 2021) - Baldesi, Giacomo; Baldini, Riccardo M.
Abstract : Emilia corallina is described as a new species endemic to the coastal area of southern Somalia close to the Kenyan border. It is closely related to E. bellioides, the only other species of the genus given for the Flora of Somalia. This narrow endemic grows in coastal dunes and madreporic limestone outcrops along the lower Juba coast and is reported at present only around the area south of Chisimaio.